Vers un nouvel ordre politique international : le traité de paix et d’amitié sino-japonais du 12 août 1978 - Colard, Daniel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1980)
On August 12th 1978 the People's Republic of China and Japan signed a treaty of peace and friendship that solemnly recognized the reconciliation between Peking and Tokyo. The original character and political, economic and geo-strategic meaning of this signal document can only be understood by placing it within Us true context. In fact, this context has two facets. The Sino-Japanese treaty can first be seen in an historical context that must be kept in mind since the « Far Eastern Question » has, from the end of the 19th century, been at the heart of Sino-Japanese and Russo-Japanese relations as well as constituting an ongoing concern for the major European powers. Prior to 1939, Japanese imperialism had succeeded in imposing its law in China and in East Asia establishing what Tokyo called a « co-prosperity sphere ». During the Second World War, the United States, Great Britain and the USSR - allies against the common enemy - had to take important decisions with regard to Japan to prepare the terms of occupation. The San Francisco Peace Treaty of 1951 established the new American-Japanese relationship. Normalization of Soviet-Japanese relations began with the signing of the joint declaration of 1956.The August 12th 1978 Peace Treaty between Peking and Tokyo can be further seen as part of specific diplomatic context comprising the Sino-Soviet conflict, East-West détente and the Sino-American rapprochement that opened the way - immediately after President Nixon's trip to China in February 1972 - for the Sino-Japanese rapprochement.Legally, the Treaty contains only five short sections, the most original of which being the « anti-hegemony » clause provided for in section 2. Diplomatically, it is not exaggerated to recognize in this Sino-Japanese agreement an element of a New International Political Order presently taking form and that has to necessarily accompany the implantation of the « New International Economic Order » that the countries of the Third World have been demanding since 1974.